KARAKTER TOKOH DALAM NOVEL LANGIT MEKAH BERKABUT MERAH KARYA GEIDURRAHMAN AL-MISHRY BERBASIS NILAI-NILAI KARAKTER RELIGIUS DAN IMPLIKASINYA DALAM PEMBELAJARAN SASTRA DI MADRASAH ALIYAH - Azizah, Aida; Setiana, Leli Nisfi (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2016)
Novel Langit Mekah Berkabut Merah work is a novel that has a lot of wisdom about religiousvalues. Religious value of these figures seen in the overall story is actualized through the elementsof the literary works of the builders. Author of the novel tells the story using language that is easyto understand and use easily understandable story line. The background of the story in the novel isparallel to the background of the life of the students, so that religious values can be utilized in theteaching of literature in class XII SMA / MA.